KINERJA GURU SMA BERSERTIFIKAT PENDIDIK DI KABUPATEN KOTAWARINGIN TIMUR - Apuanor Apuanor; Sudarmono Sudarmono; Panji Sukma Nurdilaga (STKIP MUHAMMADIYAH SAMPIT, 2020)
The purpose of this study was to determine whether there were differences in the performance of teachers who received certification allowances and had not received certification allowances at SMK Negeri 1 Kota Besi and SMK PGRI Sampit 2018/2019 academic year. This research is a qualitative descriptive study.The subjects in this study were lecturers or teachers in SMK 1 of Kota Besi and SMK PGRI Sampit totaling 48 (Forty-eight) people. Data collection techniques used are questionnaires and documentation. There is a difference in the performance of certified teachers and certified teachers whose performance is better than that of uncertified teachers